Pulmonary function impairment and its relationship with target therapy response in patients with pulmonary arterial hypertension - Xu, Xia; Xie, Mengshuang; Li, Haijun; Liu, Junjun; Yang, Zhao; Ji, Qiushang; Lu, Weida; Cui, Xiaopei (Frontiers in Medicine, 2025)
IntroductionPatients with pulmonary arterial hypertension (PAH) exhibit exertional dyspnea and decreased exercise capacity, which are not solely attributable to right heart dysfunction. Numerous studies have aimed to elucidate pulmonary function in PH patients and its correlation with disease severity and prognosis; however, the findings remain inconsistent. The impairment of ventilation and diffusion function may partially account for the occurrence of exertional dyspnea in PAH patients.MethodsThis was a single-center prospective observational study. Pulmonary function tests, right heart catheterization, and four-strata risk status stratification were performed in PAH patients. The PAH patients were followed up for 12 months.ResultsA total of 181 PAH patients were enrolled in the study, comprising 62 with idiopathic pulmonary arterial hypertension (IPAH) and heritable PAH (HPAH), 69 with PAH associated with congenital heart disease (CHD-PAH), and 50 with PAH associated with connective tissue disease (CTD-PAH). Forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), single-breath diffusion capacity for carbon monoxide (DLCO), DLCO% predicted (% pred), and reactance at 5 Hz (X5) were significantly reduced, while residual volume (RV)% pred increased in PAH patients. CHD-PAH exhibited more pronounced ventilation impairment. Six-minute walking distance (6MWD) demonstrated a positive correlation with FEV1 (r = 0.353, p < 0.01) and FVC (r = 0.373, p < 0.01), respectively. A total of 104 patients finished the follow-up. Patients exhibiting FVC% pred values below 82% demonstrated a diminished response to PAH-targeted therapy (OR = 10.553, p = 0.000, 95% CI: 2.580–43.165).ConclusionPAH patients exhibited impairment in both ventilation and diffusion capacity, while patients with diverse etiologies demonstrated distinct characteristics. FVC and FEV1 were positively correlated with 6MWD, respectively. PAH patients with FVC% pred values below 82% demonstrated a diminished response to PAH-targeted therapy.